Analisis Semiotika Puisi “Sajak Balsem untuk Gus Mus” Karya Joko Pinurbo - Rifqi Ihtifazhuddin alwafi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This article explains the semiotic analysis of Joko Pinurbo's poem “Balsem Verses for Gus Mus”. The focus of this article is on signs or conventions in poetry as a whole. Then analyzed with a semiotic study seen from the appearance of the signs put forward by the experts, taking the most visible aspects. The purpose of this research is to explain the meanings or signs in the poetry to inform the readers about the meaning of the poem. This study uses descriptive qualitative methods as steps of problem solving and finding solutions by describing the state of the research object based on the apparent reality. The poem "Balsem for Gus Mus" describes human life in a country that is in chaos, people who are never satisfied with what they already have, humans have a sick mind like crazy because they take life seriously. Every literary work in the form of poetry can be said to be one of the genres of literary works that have many benefits as an aesthetic development. The analysis results in the verses of this poem show the social phenomena described, namely low social status, high social status, greedy people and people who are diligent in worshiping but always committing sins. This research was conducted to provide an overview of the social conditions at the time of the creation of this work.